Hepatotoxicity evaluation of cannabidiol, cannabinol, cannabichromene and cannabigerol using a human quad culture liver chip - Jacob D. Larson; Sushma Jadalannagari; Jake Chaff; James Velez; Josiah Sliz; Lorna Ewart; Donna Webster; Jiang Hu (Scientific Reports)
Abstract Due to the increasing availability of hemp-derived products for recreational and medicinal use, it is imperative to understand the hepatotoxicity of the naturally occurring phytocannabinoids. Though, traditionally animal models or in vitro techniques are used to evaluate hepatotoxicity, these methods often fail due to the species differences and lack of the needed complexity. Thus, this study investigated the hepatotoxicity potential of Cannabidiol (CBD), Cannabinol (CBN), Cannabichromene (CBC), and Cannabigerol (CBG) using the Emulate Quad-Culture Liver-Chip model. Liver-Chips were dosed with three concentrations (0.24, 3, or 4.7 µM) of each cannabinoid for 7 days continuously, and acetaminophen (APAP) at 1, 3 or 10 mM dose was also tested as positive control. CBD, CBN, and CBG demonstrated the lowest hepatotoxic potential, as evidenced by unchanged liver injury markers and albumin secretion. CBN at the mid and high dose and CBD at the high dose began to show signs of toxicity on day 7 as observed through morphological changes (CBN) and proinflammatory cytokine and LDH release (CBD), suggesting that increased exposure may result in more severe toxicity. CBC treatment caused increased lactate dehydrogenase (LDH), cytokine release, and decreased albumin production, suggesting moderate hepatotoxicity. Liver-Chip also revealed varying adverse effects of cannabinoids on reactive oxygen species (ROS) and mitochondrial function in both hepatocytes and non-parenchymal cells (NPCs), giving further insights into the mechanism of liver injury. These results indicated differences in cannabinoid toxicity profiles while demonstrating the Liver-Chip model as an alternative tool for live toxicity screening.